The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1080/08035250600684453
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of recurrent complaints of pain among Greek schoolchildren and associated factors: A population‐based study

Abstract: The results are indicative of the prevalence of RCP in Greek schoolchildren. This study enlightens the psychosocial component of RCP and emphasizes the importance of gathering information on children's social background in medical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 27 publications
7
27
0
6
Order By: Relevance
“…In other studies, the frequency of stomachache was about 10%, very similar to what has been found in other studies [27,41]. The gender analysis showed no significant differences, corroborating most previous research [2,8,10,22,27,41].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In other studies, the frequency of stomachache was about 10%, very similar to what has been found in other studies [27,41]. The gender analysis showed no significant differences, corroborating most previous research [2,8,10,22,27,41].…”
Section: Discussionsupporting
confidence: 93%
“…There is a tendency to have no differences until late childhood and puberty, when symptoms are more common in girls than in boys, especially the closer they get to adolescence [2,8,10,17,22,27,41]. Nevertheless, Rask et al [42] found gender differences in preschool children, and girls showed more recurrent physical complaints.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…42,43 In our sample, 54% had experienced pain in the previous week, a higher prevalence than in the general population. [44][45][46] However, we did not study the source of the pain, which could be similar to the general pains that all children experience. Furthermore, children with poor QoL might per ceive pain diff erently or report emotional distress as pain.…”
Section: Discussionmentioning
confidence: 99%
“…Gençler, eriflkin döneme geçifl sürecinde pek çok zorlukla bafl etmek zorunda kal›rlar ve sa¤l›kl› olmalar› onlar›n zorluklarla etkin bir flekilde bafl edebilmelerini kolaylaflt›r›r. Ancak, araflt›rmalar, ergenlerin madde kullan›m›, diyet yapma, ö¤ün atlama, besin de¤eri yüksek yiyecekler yerine enerjisi yo¤un yiyecekleri tüketme, yeterince fiziksel etkinlikte bulunmama, düzenli difl f›rçalamama ve zorbal›k gibi pek çok sa¤l›¤› riske atan davran›fllar nedeni ile sa¤l›k-lar›n› k›sa ya da uzun sürede riske att›klar›n› göstermekte-dir (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Giriflunclassified